Testimony on the European debt and financial crisis - Nicolas Véron (Bruegel, 2011)
Europe's banking system has been in a state of systemic fragility since 2007-08. The current phase is marked by a sequence of interactions between sovereign problems and banking problems, resulting in gradual contagion to more countriesand more asset classes. The banking and sovereign crises are compounded by acrisis of the European Union institutions. Successful crisis resolution will need to include at least four components at theEuropean level, in addition to steps to be taken by individual countries: fiscalfederalism; banking federalism; a profound overhaul of EU/euro-area institutions;and short-term arrangements that chart a path towards the completion of theprevious three points. These requirements for crisis resolution cannot be met unless political conditionschange sharply in their favour, which leaves the United States and the global economyexposed to the risk of financial contagion. However, only the Europeansthemselves can solve their current predicament.This Policy Contribution reproduces the written statement prepared by the authorfor the hearing on The European debt and financial crisis: origins, options andimplications for the US and global economy at the Subcommittee on Security andInternational Trade and Finance of the US Senate Committee on Banking, Housing,and Urban Affairs, on 22 September 2011.
Keywords: 330; Finanzmarktkrise; Bankenkrise; Föderalismus; Finanzpolitik; Öffentliche Schulden; Wirtschaftspolitik; EU-Staaten